1998
DOI: 10.1128/mcb.18.2.694
|View full text |Cite
|
Sign up to set email alerts
|

Different cis-Acting Elements Are Involved in the Regulation of TRP1 and TRP2 Promoter Activities by Cyclic AMP: Pivotal Role of M Boxes (GTCATGTGCT) and of Microphthalmia

Abstract: In melanocytes and in melanoma cells, cyclic AMP (cAMP)-elevating agents stimulate melanogenesis and increase the transcription of tyrosinase, the rate-limiting enzyme in melanin synthesis. However, two other enzymes, tyrosinase-related protein 1 (TRP1) and TRP2, are required for a normal melanization process leading to eumelanin synthesis. In B16 melanoma cells, we demonstrated that stimulation of melanogenesis by cAMP-elevating agents results in an increase in tyrosinase, TRP1, and TRP2 expression. cAMP, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
300
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 297 publications
(311 citation statements)
references
References 43 publications
5
300
0
2
Order By: Relevance
“…Experiments using a 2.2 kb fragment of the mouse tyrosinase promoter cloned upstream of the luciferase reporter gene, have revealed that this promoter activity is strongly activated by a-MSH, cAMP elevating agents and by the over-expression of the catalytic subunit of PKA (46,47). However, the sequence analysis of this promoter has not revealed the existence of any classical CRE site, which means that PKA does not directly regulate tyrosinase expression through CREB activation.…”
Section: Camp-dependent Intracellular Pathways Involved In the Regulamentioning
confidence: 99%
“…Experiments using a 2.2 kb fragment of the mouse tyrosinase promoter cloned upstream of the luciferase reporter gene, have revealed that this promoter activity is strongly activated by a-MSH, cAMP elevating agents and by the over-expression of the catalytic subunit of PKA (46,47). However, the sequence analysis of this promoter has not revealed the existence of any classical CRE site, which means that PKA does not directly regulate tyrosinase expression through CREB activation.…”
Section: Camp-dependent Intracellular Pathways Involved In the Regulamentioning
confidence: 99%
“…Tyrosinase regulates two catalytic processes: hydrolysis of tyrosine to L-DOPA, and oxidation of DOPA to DOPA quinine [2,3] . In addition, it is well-known that microphthalmia-associated transcription factor (MITF) strongly up-regulates the expression of tyrosinase and other melanogenic enzymes, such as tyrosinase-related protein 1 (TRP1) and tyrosinase-related protein 2 (TRP2) [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…β-Actin was detected as loading control the suppression of MITF, which is consistent with previous findings that MITF is a transcription activator regulating those melanogenesis-related genes. [52][53][54] Furthermore, the process of melanosome transportation could be disturbed by miR-25. In that case, miR-25 is possibly involved in the entire pathological development of vitiligo, from the initial dysfunction to the final disappearance of melanocytes.…”
Section: Discussionmentioning
confidence: 99%